2017
DOI: 10.21009/bioma12(1).4
|View full text |Cite
|
Sign up to set email alerts
|

Struktur Komunitas Burung Di Taman Situlembang, Taman Suropati , Dan Taman Menteng, Jakarta Pusat

Abstract: Birds are one of the animals that can be encountered utilizing City Park as a habitat. The existence of birds in a habitat influenced by factors such as life support shelter and feed availability. Situlembang Park, Suropati Park, and Menteng Park has a different characteristic. The purpose of this research was to observe differences in the structure of bird communities in the three parks. This study was conducted in January-March 2015 using descriptive method with point count technique. Results of the research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
2
0
2
Order By: Relevance
“…Due to limited resources can create competition between species in a region (Ferger et al 2014). Plants play an important role as a supporting factor for birdlife (Nugroho 2016), so variations in bird species diversity are related to vegetation composition (Kiros et al 2018). In this study found distribution among identical bird species from D and E value that an indication of competition absence in utilizing available resources.…”
Section: Level Of Bird Species Diversity Evenness and Dominance In Va...mentioning
confidence: 67%
“…Due to limited resources can create competition between species in a region (Ferger et al 2014). Plants play an important role as a supporting factor for birdlife (Nugroho 2016), so variations in bird species diversity are related to vegetation composition (Kiros et al 2018). In this study found distribution among identical bird species from D and E value that an indication of competition absence in utilizing available resources.…”
Section: Level Of Bird Species Diversity Evenness and Dominance In Va...mentioning
confidence: 67%
“…Sel tetangga merupakan sel-sel epidermis yang mengelilingi sel penjaga. Sel penjaga atau sel penutup dapat membuka dan menutup sesuai dengan kebutuhan penguapan (transpirasi) pada tanaman, sedangkan sel tetangga membantu dalam pengaturan tekanan osmotik yang berhubungan dengan pergerakan sel penutup/penjaga (Nugroho et al, 2006;Hidayat, 1995). Variasi tipe stomata yang dijumpai di dalam satu suku disebabkan oleh faktor internal (sifat genetik) dan eksternal (habitat atau lingkungannya).…”
Section: Anatomi Tipe Stomata Jambu Bolunclassified
“…Takano et al [128] noted that the longevity of senior citizens increases if there are walkable green spaces. For Indonesians, listening to bird song is a form of mental healing [31], and FTS directly stimulate bird visitation [23][24][25][27][28][29]. Moreover, FTS such as guavas, jackfruit, mangos, matoas, rambutans, and tamarinds are reliable trees for reducing air pollution [131,132].…”
Section: Fts and City Servicesmentioning
confidence: 99%